"Wir müssen eine terminologische Revolution machen" : Terminologiepolitik und -planung im postsowjetischen Kasachisch - Rakhimzhanova, Saltanat (Interdisziplinäre Studien zum östlichen Europa., 2017)
Kazakh is a Turkic language that is predominantly spoken in Central Asia and has the status of a state language in the Republic of Kazakhstan. The vocabulary of the Kazakh language is in a state of upheaval triggered by the post-Soviet reform. Saltanat Rakhimzhanova examines these changes and development tendencies in the language system in her study. Among other things, she asks about the aims pursued by the language and terminology policy in Kazakhstan. How does the practical implementation of terminology planning take place? What is the terminology work like in practice? The central object of investigation is the technical lexicons of a so-called "soft", established social science on the one hand and a "hard", more recent computer science on the other. The socio-political terminology was chosen because it directly reflects socio-political change processes. The technical lexicon of computer science, on the other hand, is characterized by the fact that it mostly comes from English and is adopted into many languages ​​of the world without any change or with little orthographic adjustment. The qualitative empirical analysis of this material provides insights into the educational paths of new specialist lexicons and records the predominant working methods as well as regularities and peculiarities in the Kazakh terminology.